Antimicrobial stewardship and the hospital nurse and midwife: how do they perceive their role?. Issue 2 (27th September 2017) - Wilcock, Michael; Powell, Neil; Underwood, Frazer
Abstract : Objectives: Our aim was to determine the views of nurses and midwives in an acute hospital regarding a potential role in an antimicrobial stewardship programme. Methods: An online survey about antimicrobial stewardship was distributed to nursing and midwifery staff at the Royal Cornwall Hospitals NHS Trust. Descriptive statistics were used for analysis. Results: Eighty responses were received. Forty-three (54%) claimed to have heard the term antimicrobial stewardship. Only seven (9%) had cause to look at the hospital's antimicrobial guidelines at least once a week. Between 47 (60%) and 68 (87%) respondents agreed they should be involved in a range of stewardship roles. Constraints of time and workload, lack of knowledge and lack of adequate staff training were the three main perceived challenges to a wider role. Conclusions: Staff in this survey recognise the potential for wider antimicrobial stewardship roles. They also identify challenges to undertaking these roles. Some of these barriers could be overcome by provision of education and support; hospital pharmacists may be able to assist with this role development.